2017
DOI: 10.5604/01.3001.0010.1698
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Wrinkle Resistance Improvement of Nettle Biofibre Using Chitosan and BTCA

Abstract: In this study, the possible improvement of the antibacterial and wrinkle resistance performance of 100% nettle fabrics was investigated. To realise this aim, antibacterial and wrinkle resistance finishing processes were applied. 1,2,3,4-Butanetetracarboxylic acid (BTCA) and sodium hypophosphite (SHP) were used to impart the wrinkle resistance property. Moreover chitosan was incorporated in the finishing bath for the antibacterial property. The effects of respective treatments on the physical properties were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…It is worth noting that these two characteristics of nettle fiber, follow similar course of development in different plant densities. Similar results reported by Arik et al [10] after experimenting with chemical applications and their effect on the quality of the nettle fiber, and observed that the control sample had the highest values and while the amount of chemicals increased, so did the values of extension at break and of the strength.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It is worth noting that these two characteristics of nettle fiber, follow similar course of development in different plant densities. Similar results reported by Arik et al [10] after experimenting with chemical applications and their effect on the quality of the nettle fiber, and observed that the control sample had the highest values and while the amount of chemicals increased, so did the values of extension at break and of the strength.…”
Section: Resultssupporting
confidence: 88%
“…The tensile strength (cN/tex) as well as the Extension at break factor were measured by the use of a Tinius Olsen Strength Testing Machine (Horsham, PA, USA), according to the TS ENISO 13934-1 standard [10].…”
Section: Measurementsmentioning
confidence: 99%
“…[30][31][32][33] Due to the demand for substituting harmful chemicals, such as formaldehyde, various novel finishing agents have been studied. [34][35][36][37] To measure the tendency of forming wrinkles, the dry crease recovery angle (DCRA) values were evaluated, indicating the capability of cotton fabrics to recover. The results of the DCRA measurements are given in Table 1 and Table 2.…”
Section: Dry Crease Recovery Angle Analysismentioning
confidence: 99%
“…To achieve easy-care performance, especially for crease recovery and retention, different commercial finishing methods and chemicals were developed such as formaldehyde-based easy-care finishes (dimethyloldihydroxy-ethylene urea-DMDHEU) [6], ether derivatives of DMDHEU [7], formaldehyde-free finishes with polycarboxylic acids (1,2,3,4-butane tetracarboxylic acid, citric acid, maleic acid, succinic acid etc.) [8], carboxyl polyaldehyde sugars [9] applied by finishing treatment, foaming [1], and sol-gel technology [10]. But these commercial finishing chemicals and methods have problems with formaldehyde release, a probable human carcinogen, during manufacturing, wearing, and storage [11].…”
Section: Introductionmentioning
confidence: 99%